Konsentrasi Klorofil-a dan Hubungannya dengan Pasang Surut di Selat Lombok - Gianie, Annassita; Suteja, Yulianto; Widiastuti, Widiastuti (Journal of Marine Research and Technology, 2019)
Lombok Strait is a strait located between Bali Island and Lombok Island that has a strong current and crossed by the main trajectory of Indonesian Throughflow (ITF). ITF is a current system that connects the Pacific and Indian Ocean. When mass water ITF passes through Indonesian waters, it mixes with other water masses, resulting in a mix of two water masses from two different oceans. These differences in water mass characteristics include temperature, salinity, DO, chlorophyll, and other tracers that can be used as an indicator of productivity. This can be determined based on the availability of chlorophyll- a concentrations. Chlorophyll- a is an active pigment in phytoplankton cells that has an important role on photosynthesis process. It is essential to know the temporal fluctuations of the chlorophyll- a concentrations at both high and low tide, and the correlation between chlorophyll- a and the water quality in the Lombok Strait. This research used primary data on chlorophyll-a and water quality parameter (DO, temperature, and salinity) and secondary data regarding tides on Port of Lembar. This research used CTD SBE 911+ as a measurement of instrument. The concentration of chlorophyll- a on CTD measurement of 0 m (0.011mg/l and 0.005) and for 10m of chlorophyll- a concentration (0.014mg/l and 0.006). The fluctuations of chlorophyll- a pattern during the tides showed that at low tide, the chlorophyll- a concentration is high, and vice versa. The chlorophyll- a was situated on a depth of 0 m and 10 m and was not affected by the water quality.